The Application of Accounting Standards Towards Performance Accountability: Role of Monitoring Financial Statements As Moderating - Helda , Helda; Masruddin, Masruddin (International Journal of Digital Marketing Science, 2024)
This research aims to: 1) To test and analyze the influence of accounting standards which influence the supervision of financial reports; 2) To test and analyze the effect of performance accountability on financial report supervision; 3) To test and analyze whether the application of accounting standards and performance accountability has an effect on the supervision of financial reports. This research was conducted using a survey method with a questionnaire as a tool to obtain data. The sample was taken using a purposive sampling method, namely 120 Civil Servants who worked within the scope of the Sigi Regency Regional Apparatus Organization. The analytical tool used to process the data is PLS with the help of WarpPLS software. The research results show that the implementation of government accounting standards influences the accountability of government agency performance; supervision of financial reports affects the accountability of government agency performance; the application of accounting standards and performance accountability influences the supervision of financial reports.